Draft Annual Plan 2005-2006 Volume-III Andaman and Nicobar Administration - Planning Commission (Planning Commission, 2005)
Provision of free and compulsory Education for all children until they complete the age of 14 years is a directive principle of the Constitution of India. In this territory, Education is free for all upto +2 stage. Elementary Education upto class I to VIII have been made compulsory through out the territory. The main emphasis would be to extend primary schooling facility in habitations where such facilities are not available and also to up-grade every Second Primary School to Middle School.
Andaman and Nicobar Administration, Planning Department